ISOLASI, IDENTIFIKASI SENYAWA ALKALOID TOTAL DAUN TEMPUYUNG (Sonchus arvensis Linn) DAN UJI SITOTOKSIK DENGAN METODE BSLT (Brine Shrimp Lethality Test) - Murtadlo, Yazid (Chem Info Journal, 2013)
Abstract: Tempuyung (Sonchus arvensis L.) from asteraceae tribe is one of the plants that have some compounds, one of them is Alkaloid. There has been done isolation of alkaloid compound to ethanol extract of tempuyung dry leave using extraction and preparative TLC with eluen n-hexane: ethyl acetate: ethanol (30:2:1). Analysis carried out on pure alkaloid isolate using method of UV-vis spectrophotometer, FTIR and LC-MS. Based on the analysis using UV-Vis spectrophotometer, FTIR and LC-MS can be a compound known alkaloid contained in the leaves tempuyung including alkaloids with the basic framework isokuinolin having absorption at a wavelength of 225 nm, 253 nm, and 352 nm, has a functional group C=N, O-H, C-O, conjugated C=C, C=O, CH2, CH3 and molecular weight compounds at 444.84 g/mol. The result of activity test using method of BSLT generates rate of LC50 from ethanol extract and total alkaloid isolate respectively 61.410 ppm and 523.634 ppm , it means the ethanol extract is less toxic and total alkaloid isolate is not toxic.